Martin Luther King, Jr. : I have a dream! - Ball, Jacqueline A. (New York : Bearport Pub., 2006)
Provides a brief biography of Martin Luther King, Jr. and his commitment to civil rights and equality.
"A great shout for freedom" -- For whites only -- "I will go back to the South" -- "How could I love people who hated me?" -- First taste of freedom -- Don't ride the bus! -- Bombs and death threats -- The children's crusade -- Just the right words -- Evil in Birmingham -- A final tragedy -- "He made our nation better" -- Just the facts.
Keywords: King, Martin Luther -- 1929-1968; African Americans; Civil rights workers -- United States; Baptists -- United States -- Clergy; African Americans -- Civil rights -- History -- 20th century; Civil rights workers; Clergy; Civil rights movements -- History; African Americans